A real-world disproportionality analysis of mepolizumab based on the FDA adverse event reporting system - Li, Huqun; Wang, Chongshu; Deng, Aiping; Guo, Cuilian (Frontiers in Pharmacology, 2023)
Background: Mepolizumab has been approved by the FDA for add-on maintenance treatment of severe asthma with an eosinophilic phenotype. Real-world studies on mepolizumab-associated adverse events are limited. The present study aimed to explore mepolizumab-related adverse events based on the US Food and Drug Administration Adverse Event Reporting System (FAERS) database.Methods: A disproportionality analysis was performed to assess the safety profile of mepolizumab based on the reports from the FAERS database between October 2015 and December 2022. Demographic information, the time to onset, the safety of longterm mepolizumab exposure as well as safety in pediatric patients were also investigated.Results: A total of 736 significant preferred terms (PTs) were identified among the 1349713,497 mepolizumab-associated adverse events (AEs) reports collected from the FAERS database. The frequently reported AEs including dyspnea, fatigue, and headache were in line with drug instruction and previous studies. Unexpected significant AEs such as cough, malaise, and chest discomfort were also identified. Most AEs occurred within the first month after mepolizumab initiation. Pneumonia and wheezing were frequently reported in patients with long-term mepolizumab exposure as well as in the pediatric population.Our results were consistent with the observations in previous clinical and real-world studies. New and unexpected AE signals of mepolizumab were also identified. Close attention should be paid to the long-term safety of mepolizumab as well as safety in the pediatric population. Prospective studies are required for optimal use of mepolizumab.